Challenges in the implementation of internet of things projects and actions to overcome them. (December 2022) - Martens, Cristina Dai Prá; Silva, Luciano Ferreira da; Silva, Deivison Feitosa; Martens, Mauro Luiz
Abstract: The objective of this article is to present actions to overcome challenges in the implementation of IoT projects. The theory of environmental impact, which presents problems and coping mechanisms, was used as a theoretical lens. Using a qualitative and exploratory approach, the research initially involved a pilot study through five in-depth interviews and documentary analysis to verify the challenges of IoT. The findings of the first phase prompted a new round of interviews that was conducted with eleven professionals, making it possible to identify the main challenges and actions to implement IoT projects. The data analysis involved a cyclical coding process using ATLAS.ti software. Eight main challenges were identified in the implementation of IoT projects: administration, data collection and management; cost; innovation; the integration of technologies; an efficiency matrix; people; security; and bringing value and business solution. Seven actions to overcome the challenges were also identified: IoT architecture; scalability, sustainability, and reliability in projects; ensure security and support; information, resources, and project management; interaction of people and things; the standardization of the IoT concept; and the promotion of knowledge of technologies and processes. This article contributes to the literature primarily in its focus on description of the relationships and co-occurrence between challenges and actions. The results can guide practitioners in the implementation of IoT projects. Graphical abstract: Image 1 Highlights: Eight main challenges were identified in the implementation of IoT projects. Seven actions to overcome challenges in IoT projects implementation are presented. Challenges-actions matrix can guide practitioners in IoT projects. The relation and co-occurrence between challenges and actions is presented. A framework of problems and actions to the context of IoT projects is proposed.